2020
DOI: 10.1186/s13148-020-00857-x
|View full text |Cite|
|
Sign up to set email alerts
|

DNA methylation changes during preimplantation development reveal inter-species differences and reprogramming events at imprinted genes

Abstract: Preimplantation embryos experience profound resetting of epigenetic information inherited from the gametes. Genome-wide analysis at single-base resolution has shown similarities but also species differences between human and mouse preimplantation embryos in DNA methylation patterns and reprogramming. Here, we have extended such analysis to two key livestock species, the pig and the cow. We generated genome-wide DNA methylation and whole-transcriptome datasets from gametes to blastocysts in both species. In ooc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
85
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(93 citation statements)
references
References 76 publications
(118 reference statements)
8
85
0
Order By: Relevance
“…Preimplantation DNA demethylation has been documented in every boreoeutherian species tested to date (e.g. mice, humans, monkeys, pigs, cows, sheep, rabbits) 19,[36][37][38][39][40][41][42][43] , however early embryonic DNA methylation dynamics have not been investigated in Eutherian lineages other than Boreoeutheria, i.e Afrotheria and Xenarthra, not to mention the more distant marsupial and monotreme groups. Likewise, the functional importance of ERV activity in early developmental and placental gene expression programs has also only been demonstrated in boreoutherian species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preimplantation DNA demethylation has been documented in every boreoeutherian species tested to date (e.g. mice, humans, monkeys, pigs, cows, sheep, rabbits) 19,[36][37][38][39][40][41][42][43] , however early embryonic DNA methylation dynamics have not been investigated in Eutherian lineages other than Boreoeutheria, i.e Afrotheria and Xenarthra, not to mention the more distant marsupial and monotreme groups. Likewise, the functional importance of ERV activity in early developmental and placental gene expression programs has also only been demonstrated in boreoutherian species.…”
Section: Discussionmentioning
confidence: 99%
“…Both active and passive demethylation pathways have been implicated in the genome-wide erasure of 5mC accompanying mammalian preimplantation development [28][29][30][31][32][33][34] . Despite the extensive conservation of the TET enzymes and DNA methylation machinery throughout metazoa 35 , developmental DNA demethylation appears to be unique to placental mammals 19,[36][37][38][39][40][41][42][43] . In contrast, 5mC patterns have been found to remain constant throughout early development in all non-mammalian vertebrates examined to date 15,[44][45][46][47][48] .…”
mentioning
confidence: 99%
“…Among reproductive technologies, cryopreservation produces the most hostile conditions for embryos, and consequently, an increased number of studies have demonstrated both a direct effect on embryos and long-term effects on gene expression, proteome and metabolome on adult animals, providing a modified foetal and postnatal phenotype [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. The early stage of mammalian development from fertilisation to implantation is a period in which global changes in the epigenetic scenery take place [ 1 , 12 , 13 , 14 , 15 ]. In ART, all of those global changes take place under in vitro conditions when the embryos develop in culture conditions that attempt to mimic the uterine environment.…”
Section: Introductionmentioning
confidence: 99%
“…The research and development of different ART protocols in the porcine species, with the nal objective of improving their e ciency in a holistic sense, represents an area of increasing interest for two main reasons: rst, for the porcine species, the potential existence of an embryo market, allows farmers the exchange of genetic material without risk of disease transmission and reducing transportation costs (reviewed by [19]); second, for the human species, there is compelling evidence that the pig is an useful model to decipher the long term impact of each aspect of the ART without confounding factors such as those related to the fertility of the parents, a fact that has been recently reinforced with the discovery of the similarities between the pig and the human regarding the DNA methylation reprogramming events during the rst week of development [20].…”
Section: Discussionmentioning
confidence: 99%